Structural and Functional Characterization of Three Polyketide Synthase Gene Clusters in Bacillus amyloliquefaciens FZB 42 - Chen, Xiao-Hua (American Society for Microbiology, 2006)
Although bacterial polyketides are of considerable biomedical interest, the molecular biology of polyketide biosynthesis in Bacillus spp., one of the richest bacterial sources of bioactive natural products, remains largely unexplored. Here we assign for the first time complete polyketide synthase (PKS) gene clusters to Bacillus antibiotics. Three giant modular PKS systems of the trans-acyltransferase type were identified in Bacillus amyloliquefaciens FZB 42. One of them, pks1, is an ortholog of the pksX operon with a previously unknown function in the sequenced model strain Bacillus subtilis 168, while the pks2 and pks3 clusters are novel gene clusters. Cassette mutagenesis combined with advanced mass spectrometric techniques such as matrix-assisted laser desorption ionization-time of flight mass spectrometry and liquid chromatography-electrospray ionization mass spectrometry revealed that the pks1 (bae) and pks3 (dif) gene clusters encode the biosynthesis of the polyene antibiotics bacillaene and difficidin or oxydifficidin, respectively. In addition, B. subtilis OKB105 (pheA sfp(0)), a transformant of the B. subtilis 168 derivative JH642, was shown to produce bacillaene, demonstrating that the pksX gene cluster directs the synthesis of that polyketide.